The valley of the shadow : a Cornish mystery - Dunn, Carola (Dunn, Carola. Cornish mysteries., 2012)
While out on a walk, Eleanor Trewynn, her niece Megan, and her neighbor Nick spot a young, half-drowned Indian man floating in the water. Delerious and concussed, he utters a cryptic message about his family being trapped in a cave and his mother dying. The young man, unconscious and unable to help, is whisked away to a hospital while a desperate effort is mounted find the missing family in time. The local police inspector presumes that they are refugees from East Africa, abandoned by the smugglers who brought them in, so while the countryside is being scoured for the family, Eleanor herself descends into a dangerous den of smugglers in a desperate search to find the man responsible while there is still time.